FRI0148 IS TREATMENT ADHERENCE OF RA PATIENTS TO MTX IMPROVED BY THE SWITCH FROM ORAL TO SUBCUTANEOUS ABMINISTRATION? RESULTS FROM THE PROSPECTIVE APRIM STUDY. (June 2019) - Flipo, René-Marc; Senbel, Eric; Tropé, Sonia; Zinovieva, Elena; Courbeyrette, Agnès; Herman-Demars, Hélène
Abstract : Background: Previous studies have shown, that switching from oral to SC MTX can lead to improved efficacy and bioavailability (especially for doses ≥15mg/wk.) as well as to a decreased frequency of adverse gastrointestinal effects in patients with RA. Furthermore, some reports consider that this switch may improve treatments adherence and persistence. Objectives: The purpose of APRiM study was to investigate the treatment adherence of RA patients switching from oral to injectable MTX or between two different MTX prefilled syringes. Methods: APRiM is a prospective, observational, multicentre study, which included adult patients with confirmed RA diagnosis (ACR/EULAR 2010 criteria) already treated by either oral MTX and requiring route modification (Gr1), or SC MTX in prefilled syringe (PFS) and eligible for a device switch (to another PFS) (Gr2). The primary criterion of the study was to estimate at 6 months the proportion of patients with strong or improved of at least 1 category treatment adherence evaluated by Morisky's self-assessment (8: strong/maximum adherence, 6-7: medium adherence, <6: poor adherence) in both groups. Results: Between June 2016 and June 2017, 110 rheumatologists, at 90% with private practice, included 466 pts, 433 of which composed the analysable baseline set. Pts baseline characteristics Gr1/Gr2 were [mean (SD)]: age: 59.2 (13.0)/61.5 (12.2) yrs; RA duration: 6.5 (7.9)/9.9 (10.5) yrs; MTX use duration: 3.6 (4.6)/6.0 (5.1) yrs; DAS28: 3.9 (0.9)/3.2 (1.2); Erosive RA: 37%/53%. All pts were receiving MTX at a mean (SD) dose of 15.1 (4.0)/15.6 (4.0) mg/wk. Mean (SD) Morisky's scores were 6.5 (2.0)/6.6 (1.8) for respectively Gr1/Gr2 at baseline, they improved up to 6.9 (1.8)/7.0 (1.5) at 6 months. Adherence remained strong or improved of at least 1 category for respectively 56% and 60% of patients [Gr1/Gr2]. Proportion of patients with strong treatment adherence improved from 40% (V0) to 48% (M6) in both Gr1 and Gr2. Interestingly, when rheumatologists were asked to estimate their patients' adherence, they reported respectively 77% and 84% [Gr1/Gr2] of patients with "no missed injections". At baseline patients in the Gr1 (oral baseline) had a higher DAS28 than in Gr2, this difference was removed after 6 months of MTX SC treatment. No new safety signals were identified during this study. Conclusion: The results of the observational study APRiM revealed that less than 50% of patients are perfectly adherent to injectable MTX treatment, irrespectively of whether was their previous MTX way of administration. Though, this proportion seems to be highly overestimated by the rheumatologists. This underlies the importance of patient/physician effective communication. References: [1] Morisky DE, et al., Predictive Validity of a Medication Adherence Measure for in an Outpatient Setting. J Clin Hypertens 2008 May:348-354. [2] Krousel-Wood M, et al., New Medication Adherence Scale Versus Pharmacy Fill Rates in Seniors with Hypertension. Am J Manag Care. 2009 Jan: 59-66. [3] Morisky DE, et al., Improving the Measurement of Self-Reported Medication Nonadherence: Response to Authors. J Clin Epidemiol 2011 Mar: 255- 263. [4] Morisky Widget™, MMAS™, MMAS4™, MMAS-8™, Morisky Medication Adherence Protocol™, and Morisky Medication Adherence Scale™ is protected by U.S. and International Trademark and Copyright laws. Permission for use is required. A license agreement is available from: MMAS Research LLC, 14725 NE 20th St., Bellevue WA 98007 or dmorisky@gmail.com. Acknowledgement: Investigators and patients of APRiM study Disclosure of Interests: René-Marc Flipo Consultant for: Honoraria from Novartis as steering committe of this survey, Eric Senbel Consultant for: Nordic Pharma, Speakers bureau: Nordic Pharma, Sonia Tropé: None declared, Elena Zinovieva Employee of: Nordic Pharma, Agnès Courbeyrette Employee of: Nordic Pharma, Hélène Herman-Demars Employee of: Nordic Pharma